Secrecy performance analysis on spatial modeling of wireless communications with unmanned aerial vehicle and ground devices - Van, Cuu Ho; Nguyen, Hong-Nhu; Le, Si-Phu; Voznak, Miroslav (Institute of Advanced Engineering and Science, 2023)
In this paper, the secrecy performance of the spatial modeling for ground devices with randomly placed eavesdroppers when an unmanned aerial vehicle (UAV) acted as two hops decode and forward (DF) was investigated. We characterize the secrecy outage probability (SOP) and intercept probability (IP) expressions. Our capacity performance analysis is based on the Rayleigh fading distributions. After analytical results by Monte Carlo simulation, and the Gauss-Chebyshev parameter was selected to yield a close approximation, the results demonstrate the SOP with the average signal-to-noise ratio (SNR) between UAV and ground users among the eavesdroppers and the IP relationship with the ability to intercept the information of the ground users successfully.